Flavour production by Saprochaete and Geotrichum yeasts and their close relatives. (15th December 2017) - Grondin, Eric; Shum Cheong Sing, Alain; James, Steve; Nueno-Palop, Carmen; François, Jean Marie; Petit, Thomas
Highlights: Flavour profile of 30 strains belonging to Geotrichum and teleomorphs was determined. PCA analysis identified 4 groups of strains based on alcohol and ester production. 3 strains (group 3 and 4) produced great diversity of esters for food applications. Statistical analysis showed no significant link between VOCs and genetic diversity. Saprochaete genus was characterized by high production of esters from catabolism of branched AAs. Abstract: In this study, a total of 30 yeast strains belonging to the genera Dipodascus, Galactomyces, Geotrichum, Magnusiomyces and Saprochaete were investigated for volatile organic compound production using HS-SPME-GC/MS analysis. The resulting flavour profiles, including 36 esters and 6 alcohols compounds, were statistically evaluated by cluster and PCA analysis. Two main groups of strains were extracted from this analysis, namely a group with a low ability to produce flavour and a group producing mainly alcohols. Two other minor groups of strains including Saprochaete suaveolens, Geotrichum marinum and Saprochaete gigas were diverging significantly from the main groups precisely because they showed a good ability to produce a large diversity of esters. In particular, we found that the Saprochaete genus (and their closed relatives) was characterized by a high production of unsaturated esters arising from partial catabolism of branched chain amino-acids. These esters were produced by eight phylogenetically related strains of Saprochaete genus.